Answer:
-20
Step-by-step explanation:
(r + b − g)(b + g)
we have fom statement:
r = 9
b = 5
g= −6
so we have:
(r + b − g)(b + g)= (9+5-(-6))*(5+(-6))
(r + b − g)(b + g)= (14+6)*(-1)
(r + b − g)(b + g)= -20
Answer:its the same thing
Step-by-step explanation:
71+99=
Answer:
t=3.2c
Step-by-step explanation:
Answer:U4HTJPIOQ;UIYPOQI;JY5IOJIUUTUIA44UTUHTIU4HJFUIHU5HQWP5TJIoj8[ajhfESUFGHUPOI;ALB J'pGH[9'Hhdhbfhdhfbfgueuhrbhsrey,]po
dm y
xlrfl
Step-by-step explanation:
hgjhfkjdfmjgngntkm kjgmtmgkigkgmtntkgbkbmhgmgmfvmvmvmnvn gn
Answer:
1/12
Step-by-step explanation:
2/3=8/12
3/4=9/12
9/12-8/12=1/12